2009
DOI: 10.1105/tpc.108.061549
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation, Somatic Homologous Recombination, and Abscisic Acid Signaling Are Influenced by DNA Polymerase ϵ Mutation inArabidopsis   

Abstract: Based on abscisic acid (ABA) inhibition of seed germination and seedling growth assays, we isolated an ABA overly sensitive mutant (abo4-1) caused by a mutation in the Arabidopsis thaliana POL2a/TILTED1(TIL1) gene encoding a catalytic subunit of DNA polymerase «. The dominant, ABA-insensitive abi1-1 or abi2-1 mutations suppressed the ABA hypersensitivity of the abo4-1 mutant. The abo4/til1 mutation reactivated the expression of the silenced Athila retrotransposon transcriptional silent information (TSI) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
230
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(249 citation statements)
references
References 96 publications
(161 reference statements)
16
230
1
1
Order By: Relevance
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, pold2-1 had little effect on the ProRD29A:LUC locus in dms3-4. Like mutants of DNA replication-related proteins (Elmayan et al, 2005;Xia et al, 2006;Yin et al, 2009;Liu et al, 2010aLiu et al, , 2010b, pold2-1 failed to suppress the silenced ProRD29A:LUC in the ros1-1 mutant (Fig. 1F).…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Plant POLE has been studied in Arabidopsis and rice, including genetic analyses that have not been performed in other multicellular organisms (Jenik et al 2005;Ronceret et al 2005;Yin et al 2009;del Olmo et al 2010). Arabidopsis POLE holoenzyme possesses two catalytic subunits (POLE1A and POLE1B, also called AtPOL2a and AtPOL2b), and the regulatory subunits POLE2 (or DPB2), DPB4, and DBP3a.…”
Section: Pold and Polementioning
confidence: 99%
“…Genes encoding the POLE3 and POLE4 subunits belong to a multigenic family and are difficult to identify unambiguously in the Arabidopsis genome. Hypomorphic mutants of POLE1 (esd7/abo4/ til1) show an early flowering phenotype because of changes in the expression of key flowering genes, a process that occurs through a genetic interaction of POLE1 with LHP1 (LIKE-HET-EROCHROMATIN PROTEIN1) (Yin et al 2009;del Olmo et al 2010). …”
Section: Pold and Polementioning
confidence: 99%